Evaluation of cytotoxicity and reactive oxygen species induced by gold nanoparticles and 6 MV X-rays in human glioblastoma cells - Weimer, Rafael Diogo (2023)
Cancer is a public health problem and one of the main causes of death around the world. Numerous studies are being carried out to improve the effects of radiotherapy, focusing on the development of radiosensitizers. Gold nanoparticles (NPs) have several biomedical applications, including the possibility of being used as radiosensitizers for cancer treatment. In this context, the aim of this work was to investigate the potential effects of gold nanoparticles without coating (GNP) and aminated dextran-coated gold nanoparticles (GNP@DX-NH2) in combination or not with X-ray irradiations from a 6 MV clinical equipment, in human glioblastoma cells (U87). GNP and GNP@DX-NH2 with metallic core of 11.9 nm and 8.0 nm, respectively, were synthesized. Toxicity assays demonstrated that NPs are not toxic at concentrations up to 50 µg/mL. The evaluation of the internalization of NPs by transmission microscopy indicated that they were heterogeneously distributed in the cytoplasm, mostly aggregated within vesicles or loose in the cytoplasm. The evaluation of reactive oxygen species (ROS) after treatment with NPs for 24h indicated an increase of 38% and 54% for GNP and GNP@DX-NH2, respectively. When combined with irradiation of 2 Gy and 6 Gy, the groups treated with GNP had an approximated increase of 70% in ROS levels relative to the non-irradiated control for both radiation doses, while the groups treated with GNP@DX-NH2 induced an increase of 60% for 2 Gy and 88% for 6 Gy. The results demonstrate that this effect could be associated with the production of ROS induced mostly by the NPs before the irradiations, and only slightly increased after the combination of NPs and radiation treatment.